Pengaruh Rasio Keuangan Terhadap Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2009-2013 - Steven Sean; Viriany (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The purpose of this study is to determine the financial ratio's partial effect on financial distress in manufacturing companies prior to the period of financial distress (t-n). Financial distress is defined as a late stage of corporate decline that precedes more cataclysmic events such as bankruptcy or liquidation. Analysis of financial ratios is performed to determine the ratio that affects the probability of financial distress. The method used is the purposive sampling method. Data analysis techniques logistic regression. Hypothesis testing is done in three periods, is the period of one year before the financial distress (t-1), a two-year period before the financial distress (t-2) and a three year period before the financial distress (t-3). Results indicate that the independent variables have a partial effect on manufacturing companies. The period t-1, ratio TL/TA andÂ NI/TA affect financial distress. The period t-2, ratio NI/EQ affect financial distress. The period t-3, ratio TL/TA and NI/TA affect financial distress.